Qualitative Study on the Factors Affecting the Occurrence of Agency Problem in Microenterprise Financing in Baitul Maal wa Tamwil - Martiana, Andri; Kassim, Salina; Zakariyah, Habeebullah; Siti Raihanun (Journal of Islamic Economic and Business Research, 2024)
Baitul Maal wa Tamwil (BMT), a financial cooperative organization, managed by people, can provide informal funding for households. However, the agency problem poses challenges for financial institutions operating in that micro sector, as financiers may struggle to monitor borrower characteristics, efforts, or profitability, leading to inefficiencies in the microcredit market. Further research is needed to determine the root causes of these problems. Empirical investigations show that the recommended methodology has not been effective, indicating a need for better methodological amendments and critical reevaluation. This study investigates factors affecting agency problems in microenterprise financing using a qualitative approach. The study involved 49 participants from eight selected BMTs, academics, and regulators, who were interviewed, observed, and analyzed for in-depth understanding. Data verification was done through triangulation, and reliability was ensured through transcript review, accurate codes, and continuous comparison with codes using NVivo. According to the study's findings, member behavior, incomplete financial analysis, lack of human resources, poor communication, Sharia compliance concerns, and lack of Islamic financial literation led to agency problem in BMT. The formation of this issue is predominantly due to poor management, inadequate levels of assistance, and incompetent management. The study reveals that issues in BMT microenterprise finance are primarily due to poor management, inadequate assistance, and incompetence. The problem is exacerbated by member behavior, incomplete financial analysis, lack of human resources, poor communication, Sharia compliance concerns, and lack of Islamic financial literacy. The study recommends adopting agency theory, increasing operational efficiency, strengthening member education, and managing compliance concerns. Practical suggestions include improving regulatory frameworks and training programs.